«Խոսք» բառամիավորի ընկալումն ու բնութագիրը Ղարաբաղի բարբառում - Արզումանյան, Արմինե
Semantic field of the lexeme խոսք (meaning ‘speech’, also ‘sayings’, ‘word’, ‘language’, ‘proverb’, ‘thought’, ‘sentence’, ‘morality’, ‘right to speak’, ‘engagement agreement’, etc. in Armenian and also in the Karabakh dialect) has some interesting manifestations in Karabakh dialect that can etymologically be explained. Various derivations of the word were found in Armenian monuscripts. All the meanings of the analyzed word in Kharabakh dialect have their analogues in the Literary Armenian Standard. The word unit խոսք has specific pronunciation in the Karabakh dialect. It has often used in both in word combinations and idioms. The etymological analysis of this lexemes similar the research of the word unit խոսք in Karabakh dialect and lexemes similar to them relationships with Proto-Indo-European language, Classical Armenian (Grabar) and the Karabakh dialect are revealed. Лексическая единица խոսք (основное значение - “речь”, на армянском, а также в карабахском диалекте имеет значения “высказывание”, “слово”, “язык”, “поговорка”, “мысль”, “предложение”, “мораль” и другие) имеет различную семантику в карабахском диалекте, что объясняется его этимологией. В армянских письменных памятниках данное слово сохранилось с разными вариантами словообразования. Используемые в карабахском диалекте все значения слова խոսք имеются в современном литературном армянском языке. Слово խոսք имеет характерное для карабахского диалекта произношение. Часто используется как в идиомах, так и в свободной речи. С исследованием данного слова, а также подобных лексических единиц становится видимым взаимоотношение карабахского диалекта с индоевропейским языком, а также с классическим армянским языком (Грабар).
Keywords: Հայոց լեզու